Arousal and Executive Alterations in Attention Deficit Hyperactivity Disorder (ADHD) - Martella, Diana; Aldunate, Nerea; Fuentes, Luis J.; Sánchez-Pérez, Noelia (Frontiers in Psychology, 2020)
Attention Deficit Hyperactivity Disorder is the most common neurobehavioral disorder of childhood and can significatively affect personal and social development and academic achievement. Taking in to account the model of attentional networks proposed by Posner and colleagues (1990), the aim of the present study was to review the literature about two main explicative models of ADHD, the Inhibition Model (Barkley, 1997, 2000) and the Cognitive-Energetic Model (Sergeant, 2000; J. A. Sergeant, 2005), discussing behavioral and neurological evidences and limitations of both hypotheses. The review indicated many evidences in favor of the energetic model and pointed to an unstable arousal as a potential pathogenetic factor in ADHD.